Adolescent Experiences with Self-Asphyxial Behaviors and Problematic Drinking in Emerging Adulthood. (July 2021) - Austin, Jillian E.; Lang, Amy C.; Nacker, Anna M.; Wallace, Alexander L.; Schwebel, David C.; Brown, B. Bradford; Davies, W. Hobart
Self-asphyxial behavior to achieve a euphoric high (The Choking Game; TCG), occurs most often during early adolescence. Participants in TCG often engage in other risky behaviors. This study investigated the relationship between prior experience with TCG and problematic drinking behaviors in emerging adulthood. Emerging adults, 18 to 25 years old (N = 1248), 56% female, and 78% Caucasian completed an online survey regarding knowledge of and prior engagement in TCG and current drinking behaviors. Participants who personally engaged in TCG during childhood/adolescence or were familiar with TCG reported significantly more problematic drinking behaviors during emerging adulthood. Those present when others engaged in TCG but resisted participation themselves reported significantly less current problematic drinking behaviors than those who participated, but significantly more current problematic drinking behaviors than those never present. Emerging adults with increased social familiarity with TCG during adolescence endorsed greater problematic drinking behaviors. Results suggest resistance skills may generalize across time/activities.